Correction: Surface nanobubbles on the carbonate mineral dolomite. Issue 37 (8th July 2019) - Owens, Camilla L.; Schach, Edgar; Rudolph, Martin; Nash, Geoffrey R.
Abstract : Correction for 'Surface nanobubbles on the carbonate mineral dolomite' by Camilla L. Owens et al., RSC Adv., 2018, 8, 35448–35452.